All the missing pieces eaudiobook - Cowles, Catherine (Shady Cove., 2025)
Sometimes the last thing you expect is exactly what you need, the final missing piece. And sometimes it comes in the form of a towering, broody sheriff, determined to get in your way at every step. Ridley Sawyer knows what it's like to miss someone, to feel like a piece of her vanished—because it happened to her the night her twin sister disappeared. Now, Ridley channels that loss into hope, traveling the country covering cold cases for her true crime podcast. She might not have found justice for her sister but that doesn't stop her from finding it for others. Until Sheriff Colter Brooks gets in her way. Colt knows what it's like to have reporters descend on his town in the wake of a tragedy, and he's not about to let a fiery podcaster stir up trouble. It doesn't matter that her haunting blue eyes tell him there's more to Ridley's story or that he can't stop imagining what it would be like to touch her. But when Ridley's cold case turns hot and she's thrust into the crosshairs, Colt has no choice but to step in. Suddenly, Ridley's living at his house, drinking his whiskey, and stealing his dog's affections. But she's also proving that she's so much more than his first impression. And as they get closer to the truth, the game they've been playing might just turn deadly...